2015
DOI: 10.7763/ijesd.2015.v6.597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dissolved Oxygen Concentrations on Specific Microbial Activities and Their Metabolic Products in Simultaneous Sulfur and Nitrogen Removal

Abstract: 0 yields decreased significantly. In addition, SRB activity was inhibited significantly while activity of SOB was not significantly different. In contrast, the activity of nitrifier was enhanced by increasing oxygen to peak removal of ammonium. However, N 2 gas production was increased slightly because nitrate reduction to N 2 was inhibited at high DO concentrations.Index Terms-Simultaneous removal, sulfate, ammonium nitrogen, specific microbial activity, metabolic product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The characteristics of the CLW influent were 1200 ± 85 mg L −1 SO 4 2− ‐S, 235 ± 42 mg L −1 NH 4 + ‐N, 4350 ± 125 mg L −1 COD, 820 ± 44 mg L −1 volatile fatty acids (VFAs), 1300 ± 30 mg L −1 alkalinity and pH 5.0, which was adjusted to pH 7.0 before being fed to the MOHR. Inoculum seeds derived from an anaerobic open pond of a swine farm were added at 20 g L −1 to the CLW, which was a suitable source of inoculum sludge from a previous study of Thongnueakhaeng and Chaiprasert . The CLW influent was continuously upflow fed into the MOHR using a peristaltic pump.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the CLW influent were 1200 ± 85 mg L −1 SO 4 2− ‐S, 235 ± 42 mg L −1 NH 4 + ‐N, 4350 ± 125 mg L −1 COD, 820 ± 44 mg L −1 volatile fatty acids (VFAs), 1300 ± 30 mg L −1 alkalinity and pH 5.0, which was adjusted to pH 7.0 before being fed to the MOHR. Inoculum seeds derived from an anaerobic open pond of a swine farm were added at 20 g L −1 to the CLW, which was a suitable source of inoculum sludge from a previous study of Thongnueakhaeng and Chaiprasert . The CLW influent was continuously upflow fed into the MOHR using a peristaltic pump.…”
Section: Methodsmentioning
confidence: 99%
“…found that ammonium removal efficiency reached about 96% at DO 0.30 mg L −1 for partial nitrification resulting in the production of nitrite. Moreover, Thongnueakhaeng and Chaiprasert reported the optimal DO concentration in simultaneous removal of sulfur and nitrogen compounds as 0.10–0.15 mg L −1 , providing sulfate and ammonium removal efficiencies of 71.2 and 62.8% respectively. Apart from the aforementioned DO parameter, a COD/SO 4 2− ratio of 3:2 achieved 100% sulfate and nitrate removal efficiencies with a granule formation consisting of SRB and DNB communities .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation